Can participatory workplace interventions aimed at changing sedentary time also reduce musculoskeletal symptoms in office workers? - Parry, Sharon; Straker, Leon; Gilson, N.; Smith, Anne (Human Factors and Ergonomics Society of Australia Inc. (HFESA), 2013)
Background: Occupational sedentary behaviour is an important contributor to overall sedentary risk. To date, there is limited evidence for effective workplace interventions to reduce occupational sedentary time and increase light activity during work hours. Further, very few studies have examined how changes in sedentary behaviour can impact musculoskeletal symptoms of office workers. Aims: To determine if participatory workplace interventions could reduce total sedentary time, sustained sedentary time (bouts > 30 minutes), increase the frequency of breaks in sedentary time and promote light intensity activity during work hours. Further, the study aimed to assess if changes in sedentary behaviour would also modify self-reported musculoskeletal symptoms. Methods: A randomised controlled trial was conducted with clerical, call centre and data processing workers in 3 large government organisations in Perth, Australia. Three interventions were developed using a participatory approach. Participants wore an accelerometer for one week at the start and end of the 12 week intervention period. Musculoskeletal symptoms before and after the intervention were assessed with the Nordic Musculoskeletal Questionnaire. Results: For all participants there was a significant reduction in sedentary time during work hours, a significant increase in the number of breaks/sedentary hour during work hours and a concurrent significant increase in light activity during work hours. There were no significant changes in musculoskeletal symptoms following the intervention. Conclusions: Participatory workplace interventions can reduce sedentary time, increase the frequency of breaks and improve light activity of office workers by using a variety of interventions. The interaction between sedentariness and musculoskeletal symptoms requires further investigation.